Adsorption of Basic Dyes Crystal Violet on Agricultural Biomass: Characterization, Isotherm, and Kinetic Studies - Kristanti, Risky Ayu; Yuniarto, Adhi; Hadibarata, Tony (International Journal of Integrated Engineering, 2022)
The removal of crystal violet (CV) dye from aqueous solution using agricultural waste-based adsorbent was investigated. Two adsorbents, lime peels (Citrus aurantifolia) and pineapple leaves (Ananas comosus) at different quantities (1, 3, 5, 7 and 10 g) were tested to 50 mL of CV solution (1,000 mg/L) at 3-hours interval incubation. The characterization of adsorbents was performed by FESEM and FTIR to explain adsorbent’s properties and structure. The results showed that lime peels and pineapple leaves removed 98% and 97% of CV dye, respectively. Under FESEM analysis, the surface structure of adsorbent that perforated and the presence of polymer were attributable to the adsorption ability. Indeed, FTIR analysis confirmed the attendance of carboxyl and carbonyl group that caused the enhancement of adsorption process.Keywords: crystal violet, basic dye removal, agricultural based-adsorbent